Oxidative stress in cows with acute puerperal metritis - Kizil, O.; Akar, Y.; Yuksel, M.; Saat, N. (Ecole Nationale Veterinaire Toulouse, 2010)
The aim of this study was to compare the oxidant / antioxidant balance between cows with acute puerperal metritis (n = 12) and healthy controls (n = 12) by measurement of MDA concentrations, antioxidant GSHPx (glutathione peroxidase) and catalase enzyme activities and concentrations of chain breaking antioxidant vitamins (A, E, C and beta-carotene) in plasma determined by spectrophotometry methods. The acute puerperal metritis was clinically diagnosed and the mean MDA concentration was significantly higher in the diseased group than in controls whereas the mean enzyme activities and mean beta-carotene and vitamin concentrations were markedly and significantly depressed. Moreover, 3 affected cows exhibited abnormal high values of MDA concentrations and at least, one antioxidant marker was altered M 9 cows. These results demonstrate the occurrence of an oxidative stress in cows with acute puerperal metritis which is exacerbated throughout antioxidant overutilization.
Keywords: Cow; puerperal metritis; lipid peroxidation; antioxidant; glutathione peroxidase; catalase; vitamin C; vitamin A; vitamin E; beta-carotene